Effects of noninvasive brain stimulation on motor functions in animal models of ischemia and trauma in the central nervous system - Seda Demir; Gereon R. Fink; Maria A. Rueger; Stefan J. Blaschke (Neural Regeneration Research)
Noninvasive brain stimulation techniques offer promising therapeutic and regenerative prospects in neurological diseases by modulating brain activity and improving cognitive and motor functions. Given the paucity of knowledge about the underlying modes of action and optimal treatment modalities, a thorough translational investigation of noninvasive brain stimulation in preclinical animal models is urgently needed. Thus, we reviewed the current literature on the mechanistic underpinnings of noninvasive brain stimulation in models of central nervous system impairment, with a particular emphasis on traumatic brain injury and stroke. Due to the lack of translational models in most noninvasive brain stimulation techniques proposed, we found this review to the most relevant techniques used in humans, i.e., transcranial magnetic stimulation and transcranial direct current stimulation. We searched the literature in PubMed, encompassing the MEDLINE and PMC databases, for studies published between January 1, 2020 and September 30, 2024. Thirty-five studies were eligible. Transcranial magnetic stimulation and transcranial direct current stimulation demonstrated distinct strengths in augmenting rehabilitation post-stroke and traumatic brain injury, with emerging mechanistic evidence. Overall, we identified neuronal, inflammatory, microvascular, and apoptotic pathways highlighted in the literature. This review also highlights a lack of translational surrogate parameters to bridge the gap between preclinical findings and their clinical translation.